2008
DOI: 10.1029/2007jg000550
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground biomass and leaf area index (LAI) mapping for Niassa Reserve, northern Mozambique

Abstract: [1] Estimations of biomass are critical in miombo woodlands because they represent the primary source of goods and services for over 80% of the population in southern Africa. This study was carried out in Niassa Reserve, northern Mozambique. The main objectives were first to estimate woody biomass and Leaf Area Index (LAI) using remotely sensed data [RADARSAT (C-band, l = 5.7-cm)] and Landsat ETM+ derived Normalized Difference Vegetation Index (NDVI) and Simple Ratio (SR) calibrated by field measurements and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 40 publications
4
62
0
Order By: Relevance
“…The impact of fires on biomass and carbon stocks has been addressed in a few countries. [53] in Zimbabwe, [54] and [31] in Zambia, and [46] and [55] in Mozambique have observed that fire protected sites had more woody biomass than frequently burned sites.…”
Section: Biomass and Carbon Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of fires on biomass and carbon stocks has been addressed in a few countries. [53] in Zimbabwe, [54] and [31] in Zambia, and [46] and [55] in Mozambique have observed that fire protected sites had more woody biomass than frequently burned sites.…”
Section: Biomass and Carbon Dynamicsmentioning
confidence: 99%
“…Woody biomass was observed to range from 1.5 Mg ha -1 (3-6 years old coppice) to 144 Mg ha -1 (mature wet Miombo) [9,[41][42][43][44][45]. Dry Miombo ranges between 53-55 Mg ha -1 [45][46][47][48]. It is confirmed that wood and soil compartments are the most important of these stocks [48][49], but grass, litter and root may contribute significantly to carbon sequestration.…”
Section: Biomass and Carbon Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arg.) Pichon [51]. In southwestern Tanzania, [50] reported a tree species diversity score (Shannon-Wiener diversity) of 3.44 versus 2.86 in the Miombo woodlands subjected to low and high rates of resource use, respectively.…”
Section: Diversity and Population Structure Studiesmentioning
confidence: 99%
“…In the Niassa National Reserve (NNR), one of the most pristine and least disturbed areas of Africa's deciduous Miombo woodlands, notable alterations in vegetation structure and composition were reported in areas with high ire (mostly anthropogenic) frequency [51,52].…”
Section: Diversity and Population Structure Studiesmentioning
confidence: 99%